Chewing lice (Phthiraptera) from typical antbirds and ground ant-birds (Passeriformes: Thamnophilidae, Formicariidae) from Costa Rica, with descriptions of three new species of the genera Formicaphagus and Myrsidea - Sychra, Oldãich; Literák, Ivan; Capek, M.; Havlcek, Martin (Zootaxa, 2006)
Descriptions and illustrations are given for one new species of Formicaphagus Carriker, 1957 and two new species of Myrsidea Waterston, 1915 from typical antbirds and ground antbirds from Costa Rica. They and their type hosts are: Formicaphagus tyrannina ex Cercomacra tyrannina (Thamnophilidae), Myrsidea mcleannani ex Phaenostictus mcleannani (Thamnophilidae) and Myrsidea klimesi ex Formicarius analis (Formicariidae). These are the first records of Myrsidea from members of the passerine families Thamnophilidae and Formicariidae. Records of two other known louse species, one of Formicaphagus and one of Machaerilaemus Harrison, 1915, both from thamnophilid hosts, are also discussed.